Thermal Interface Materials
By using a wide-particle distribution thermal filler and a low molecular weight polyol or polymer matrix, combined with surface modification technology, the shortcomings of existing thermoelectric contact materials in terms of thermal conductivity, fluidity and wear resistance are solved, and efficient and economical thermal management effects are achieved.
Patent Information
- Application Number
- JP2021569016
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-05-21
- Filing Date
- 2020-04-22
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2040-04-22
AI Technical Summary
Existing thermoelectric contact materials have shortcomings in thermal conductivity, fluidity, wear resistance and cost of filling materials, and it is difficult to meet the needs of efficient thermal management.
Thermal conduction fillers with a wide particle size distribution and low molecular weight polyols or polymers are used as substrates to improve the flowability and wear resistance of the filler through surface modification, and improve thermal conductivity by optimizing the filler concentration and particle size distribution.
The combination of high thermal conductivity (≥2.0 W/mK), low viscosity and non-wear fill materials is achieved, reducing production costs and improving the overall performance of thermoelectric contact materials.
Smart Images

Figure 0007662537000006 
Figure 0007662537000007 
Figure 0007662537000008
Abstract
Description
[Technical field]
[0001] The teachings herein are generally directed to thermal interface materials having high thermal conductivity, components and articles including the thermal interface materials, and related methods. The thermal interface materials include an oligomeric or polymeric matrix phase and one or more thermally conductive fillers dispersed in the matrix phase. [Background technology]
[0002] In the automotive industry, a trend towards reducing the weight of vehicles has occurred in the last decade. This lightweight trend has been mainly driven by regulations to reduce vehicle CO2 emissions. In recent years, lightweight construction strategies have been further promoted by the increase in the number of electric vehicles. The combination of the growing automotive market and the growing market share of electric vehicles will result in a high growth in the number of electric vehicles. It is necessary to provide high range batteries with high energy density. Several battery strategies are currently following concepts that differ in details, but what all long-range endurance battery concepts have in common is the need for thermal management. In particular, thermal interface materials are required to thermally connect the battery cells or modules with the cooling unit.
[0003] Various compositions including conductive fillers are described in PCT Publication Nos. WO 2001 / 041213 A1, WO 2014 / 047932 A1, WO 2015 / 148318 A1, WO 2016 / 145651 A1, WO 2017 / 091974 A1, WO 2018 / 34721, and WO 2006 / 016936 A1, European Patent Application No. 1438829 A1, Japanese Patent Publication No. 2010 / 0138357, and U.S. Patent Application Publication No. 2009 / 0250655 A1, each of which is incorporated by reference in its entirety. In these prior attempts, the compositions suffered from one or more of the following needs for inexpensive thermal interface materials: the compositions had poor thermal conductivity, the compositions were difficult to manufacture, the compositions did not adequately fill gaps resulting in poor contact, the compositions required expensive materials, or the compositions required abrasive fillers that could damage processing equipment. Summary of the Invention [Problem to be solved by the invention]
[0004] There continues to be a need for thermal interface materials that have both high thermal conductivity and low viscosity. There also continues to be a need for thermal interface materials that have non-abrasive filler materials. There also continues to be a need for thermal interface materials that are more economical in terms of raw material costs and / or manufacturing / processing costs. [Means for solving the problem]
[0005] One or more of the above needs may be accomplished using thermal interface materials in accordance with the teachings herein.
[0006] One embodiment of the teachings herein is directed to a composition comprising a continuous matrix phase comprising an oligomer or polymer, and a dispersed filler phase comprising one or more fillers dispersed within the matrix phase, wherein the one or more fillers have a D of about 3 or greater. 90 / D 50and wherein one or more fillers contained therein are coated with and / or reacted with a surface modifier.
[0007] Yet another embodiment in accordance with the teachings herein is directed to a composition comprising a continuous matrix phase comprising an oligomer or polymer, and a dispersed filler phase comprising at least about 86 weight percent of one or more conductive fillers dispersed within the matrix phase, wherein the one or more conductive fillers have a D of at least about 3. 90 / D 50 It has a wide particle size distribution characterized by the ratio of
[0008] Various embodiments according to the teachings herein may further be characterized by one or various combinations of the following properties: the composition is a thermal interface material having a thermal conductivity of about 2.0 W / mK or more (preferably about 2.5 W / mK or more, more preferably about 3.0 W / mK or more); the one or more fillers are conductive fillers (i.e., thermally conductive fillers) having a thermal conductivity of about 3 W / mK to about 80 W / mK; the conductive filler is a thermally conductive filler having a thermal conductivity of about 60 W / mK or less (e.g., about 40 W / mK or less, or about 20 W / mK or less). the conductive filler comprises one or more metal atoms, where the concentration of the one or more metal atoms is about 25 percent or less, based on the total number of atoms in the conductive filler; the conductive filler comprises aluminum hydroxide; the conductive filler has a Mohs hardness of about 6 or less, preferably about 5 or less, and more preferably about 4 or less; the oligomer or polymer has a weight average molecular weight of about 15,000 g / mol or less, or about 10,000 g / mol or less. the oligomer or polymer comprises an alkoxide group; the surface modifier comprises an alkyl group having about 6 or more (preferably about 8 or more, or about 10 or more, or about 12 or more) carbon atoms and a functional group covalently bonded at one end to the filler; the surface modifier is present in an amount of about 0.05 weight percent or more (preferably about 0.2 weight percent or more, more preferably about 0.5 weight percent or more), based on the total weight of the composition; the surface modifier is present in an amount of about 10 weight percent or less, preferably about 8 weight percent or less, more preferably about 6 weight percent or less, and most preferably about 4 weight percent or less; the amount of the one or more fillers is about 86 weight percent or more, based on the total weight of the composition; the amount of the one or more fillers is about 95 weight percent or less; the one or more functional groups of the surface modifier comprise an alkoxysilane group; the composition mixes as a smooth material without crumbling; the composition has a compressibility of about 700 N or less (0.or the combined amount of the matrix phase oligomer or polymer, surface modifier (if present), and one or more fillers (e.g., conductive filler or ATH) is about 95 weight percent or more (preferably about 97 weight percent or more, or about 99 weight percent or more, or about 100 weight percent) based on the total weight of the composition.
[0009] Yet another embodiment is directed to an article comprising a layer of a composition according to the teachings herein. The article may comprise a first component to generate heat and / or a second component to remove heat. Preferably, the article comprises both a first component and a second component, and a layer is interposed between the first and second components, and the layer provides a path for heat to flow from the first component to the second component. Preferably, the first component comprises a battery.
[0010] Yet another aspect is directed to a method for cooling a device comprising generating heat in a first component and transferring the heat to a second component by flowing the heat through a thermal interface component, where the thermal interface component is formed from a composition in accordance with the teachings herein. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 illustrates the characteristics of a composition having a filler with a generally narrow particle size distribution (A), a composition having a filler with a generally broad particle size distribution (B), and a composition having a surface-modified filler with a generally broad particle size distribution (C). [Diagram 2] FIG. 1 illustrates the characteristics of a reaction between a surface modifier and a conductive filler, for example, the surface modifier can change the hydrophobicity of the surface. [Diagram 3]FIG. 1 shows exemplary compositions having various amounts of filler, where filler (A) has a narrow particle size distribution, (B) has a broad particle size distribution, and (C) has a broad particle size distribution and a surface modifier to reduce or minimize bonding between the matrix phase material and the filler. [Figure 4] 1 is an optical micrograph of an exemplary conductive filler having a broad particle size distribution. [Diagram 5] 1A-1C illustrate exemplary features of a device including a thermal interface material. [Figure 6] FIG. 1 is an exemplary diagram of a battery including a thermal interface material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Unless otherwise specified, the term "consisting essentially of" includes amounts of about 90 weight percent or more, about 95 weight percent or more, about 98 weight percent or more, or about 99 weight percent or more.
[0013] Unless otherwise specified, the terms "conductive" and "conductivity" refer to "thermally conductive" and "thermal conductivity."
[0014] The thermal interface material comprises two or more phases, preferably two phases. The first phase of the thermal interface material is a matrix phase. The matrix phase is preferably a continuous phase. However, the matrix phase may be a co-continuous phase and / or may comprise one or more subphases. Preferably, the matrix phase comprises, consists essentially of, or consists entirely of one or more polymers, oligomers, or polymerizable compounds. The matrix phase preferably comprises, consists essentially of, or consists entirely of one or more materials that are liquid at room temperature or require minimal heating to liquefy. The second phase is a discontinuous phase that is dispersed in the matrix phase. It will be understood that the discontinuous phase may be coated with one or more additional phases that provide an interface between the discontinuous phase and the matrix phase. Typically, the matrix phase comprises a material that generally has a low thermal conductivity (e.g., about 1 W / mK or less, or about 0.2 W / mK or less), so that the thermal conductivity of the composition depends primarily on the discontinuous phase. The discontinuous phase comprises one or more filler materials that are solid at room temperature. Because the filler phase is required to provide much of the heat transport, it is necessary to include high concentrations of filler to overcome the fact that the filler particles are generally dispersed in the matrix phase.
[0015] Molecular weight (i.e. weight average molecular weight) When mixed with a filler, the matrix phase material preferably has a low molecular weight so that it can flow easily and bind with a large amount of filler (e.g., as described herein). Preferably, the matrix phase material is low enough in molecular weight that it is liquid at room temperature. When mixed with a filler, the matrix phase material may have a molecular weight of about 40,000 g / mole or less, about 15,000 g / mole or less, about 10,000 g / mole or less, about 8,000 g / mole or less, about 6,000 g / mole or less, or about 4,000 g / mole or less. The matrix phase material may have a molecular weight of about 200 g / mole or more, about 400 g / mole or more, about 600 g / mole or more, about 800 g / mole or more, or about 1000 g / mole or more.
[0016] The matrix phase may be characterized by a melting temperature at or near room temperature or may be amorphous and not crystallize. The matrix phase may be characterized by one or more glass transition temperatures. Unless otherwise specified, melting and glass transition temperatures are measured using differential scanning calorimetry according to ASTM D3418-15 at a heating rate of 10°C / min.
[0017] Preferably, the matrix phase is liquid at a temperature of about 75° C. and does not exhibit any glass transition temperature above 75° C. More preferably, the matrix phase is liquid at a temperature of about 40° C. and does not exhibit any glass transition temperature above 40° C. Most preferably, the matrix phase is liquid at a temperature of about 20° C. (or even about 5° C.) and does not exhibit any glass transition temperature above 20° C. (or even above 5° C.). As such, the neat matrix phase material should be pumpable at temperatures of about 75° C., about 40° C., about 20° C., or about 5° C.
[0018] The matrix phase material may have a molecular weight that is increased, for example, by polymerization, crosslinking, or curing. If the molecular weight of the matrix material is increased, such reaction preferably occurs after the matrix material is mixed with a filler. For example, the molecular weight may be increased after the composition is applied, alone or with one or more other components, onto a surface of a device where thermal management is required. The one or more other components may include compounds that mix and / or react with the matrix phase material. When the molecular weight of the matrix phase material is increased, it is preferably high enough that the matrix phase does not flow. For example, the matrix phase may be crosslinked so that it does not flow, and / or the glass transition temperature of the matrix phase material may be increased to about 30° C. or higher, about 50° C. or higher, about 70° C. or higher, or about 90° C. or higher.
[0019] The matrix phase material may be an organic material having a backbone containing carbon atoms or may be a silicon-based material having a backbone containing silicon atoms (e.g., -Si-O- groups). Organic materials include oligomers and polymers that include one or more monomers selected from the group consisting of olefins, alkoxides, carbonates, acrylates, acrylonitriles, dienes, bisphenols, diacids, diamines, diols, and isocyanates. For example, the matrix phase material may include, consist essentially of, or consist entirely of alkoxide oligomers or polymers. Preferred alkoxides include ethylene oxide, propylene oxide, and butylene oxide.
[0020] The matrix phase material may contain reactive groups or may generally be free of reactive groups. For example, the alkoxide oligomer or polymer molecule may be end-capped so that it generally does not have reactive OH groups. Alternatively, the alkoxide oligomer or polymer molecule may be a linear molecule with OH groups at one or both ends. It is also possible for the alkoxide oligomer to have a branched structure with three or more arms. Such structures may have no OH groups, a single OH group, two OH groups, three OH groups, or four or more OH groups. For example, the alkoxide oligomer may be initiated with glycerin and therefore have three arms. Each of the arms may have an OH group, or one or more of the arms may be end-capped. The end-capping may be with a terminal alkyl group (preferably a methyl, ethyl, propyl, or butyl group) to form an ester group.
[0021] filling material The composition according to the teachings herein includes one or more fillers to increase the thermal conductivity of the composition. The fillers may include ultra-high conductive fillers (e.g., fillers having a thermal conductivity of about 100 W / mK), but such fillers are typically abrasive and / or expensive. Preferably, the one or more fillers include, consist essentially of, or consist entirely of one or more conductive fillers having a thermal conductivity of about 80 W / mK or less, about 50 W / mK or less, about 30 W / mK or less, about 20 W / mK or less, or about 15 W / mK or less. The conductive fillers preferably have a thermal conductivity of about 3 W / mK or more, about 4 W / mK or more, about 5 W / mK or more, or about 6 W / mK or more. The conductive fillers may be characterized by a thermal conductivity of about 10+ / -10%, about 10+ / -20%, or about 10+ / -30%. Preferably, the amount of superconductive filler in the composition is about 15 weight percent or less, more preferably about 4 weight percent or less, even more preferably about 1 weight percent or less, and most preferably about 0.3 weight percent or less, based on the total weight of the one or more fillers. The amount of superconductive filler in the composition can be about 0.0 weight percent or more, based on the total weight of the one or more fillers. The amount of conductive filler (i.e., superconductive filler) can be about 80 weight percent or more, about 85 weight percent or more, about 90 weight percent or more, about 93 weight percent or more, about 96 weight percent or more, about 98 weight percent or more, about 99 weight percent or more, or about 99.7 weight percent or more, based on the total weight of the one or more fillers. The amount of conductive filler can be about 100 weight percent or less, based on the total weight of the one or more fillers.
[0022] When present, the superconductive filler can be any filler that has a thermal conductivity of about 100 W / mK. Examples of superconductive fillers include boron nitride and aluminum powder.
[0023] The conductive filler can be any filler having thermal conductivity, such as those described herein. For example, the conductive filler can have a thermal conductivity of about 3 W / mK to about 80 W / mK. The conductive filler is preferably non-abrasive (e.g., less abrasive than boron nitride, less abrasive than aluminum powder, or both). An example of a non-abrasive conductive filler is aluminum hydroxide (i.e., ATH) powder. Aluminum hydroxide powder has a thermal conductivity of 3 to 80 W / mK (typically about 10 W / mK).
[0024] Conductive fillers typically contain one or more metal or metalloid atoms and one or more nonmetal atoms. Metalloid atoms include boron, silicon, germanium, arsenic, antimony, and tellurium. Preferred metal atoms include alkali metals, alkaline earth metals, transition metals, and post-transition metals. The amount of nonmetal atoms in the conductive filler should be high enough so that the conductive filler is not hard and abrasive. Examples of hard and abrasive metal or metalloid-containing fillers include SiC, TiC, and BN. These hard and abrasive abrasive fillers contain 50 atomic percent of metal or metalloid. Preferably, the concentration of nonmetal atoms in the conductive filler is greater than about 50 atomic percent of nonmetal atoms, more preferably about 65 percent or more, even more preferably about 75 percent or more, and most preferably about 80 percent or more, based on the total number of atoms in the conductive filler. The concentration of non-metallic atoms may be about 95 atomic percent or less, about 93 atomic percent or less, about 90 atomic percent or less, or about 88 atomic percent or less. The conductive filler preferably has a sufficient concentration of metal atoms such that the thermal conductivity is about 3 W / mK. The combined concentration of any metals and metalloids in the conductive filler is preferably about 5 atomic percent or more. The combined concentration of any metals and metalloids in the conductive filler may be less than 50 atomic percent, about 35 atomic percent or less, about 25 atomic percent or less, or about 20 atomic percent or less.
[0025] A preferred composition includes a sufficient amount of conductive filler such that the thermal conductivity of the composition is about 1.5 W / mK or more, preferably about 2.0 W / mK or more, more preferably about 2.5 W / mK or more, and most preferably about 3.0 W / mK or more. The thermal conductivity of the composition is typically about 10 W / mK or less, about 7 W / mK or less, or about 5 W / mK or less. If the amount of conductive filler is too low, the composition will not be able to conduct enough heat to manage the temperature of the device. To achieve such high thermal conductivity of the composition, the composition typically has a high concentration of conductive filler. Preferably, the amount of conductive filler in the composition is about 60 weight percent or more, more preferably about 70 weight percent or more, even more preferably about 75 weight percent or more, even more preferably about 80 weight percent or more, even more preferably about 85 weight percent or more, and most preferably about 88 weight percent or more, based on the total weight of the composition. The amount of conductive filler in the composition should be low enough that the conductive filler can be dispersed in the matrix. Typically, the amount of conductive filler is about 95 weight percent or less, and more preferably about 92 weight percent or less, based on the total weight of the composition.
[0026] The conductive filler preferably has a Mohs hardness that is low enough so that the conductive filler is generally non-abrasive. Preferably, the conductive filler has a Mohs hardness of about 7.0 or less, preferably about 5.0 or less, and most preferably about 4.0 or less. The conductive filler may have a Mohs hardness of about 0.5 or more, about 1.5 or more, or about 2.0 or more.
[0027] Conductive fillers typically contain MX bonds, where M is a metal and X is a nonmetal. Preferably, the ratio of MX bonds to MM bonds (metal-metal bonds) in the filler can be about 2.0 or more, about 3.0 or more, or about 4.0 or more. It is understood that conductive fillers may not contain MM bonds. An example of a conductive filler that is generally free of MM bonds is aluminum hydroxide.
[0028] Particle size distribution To achieve a combination of high thermal conductivity of the composition and the ability to mix and process the composition, the conductive filler preferably has a broad particle size distribution.
[0029] A broad particle size distribution may allow the particles to pack more efficiently. The particle size distribution of the conductive filler may be measured using laser diffraction. The particle size distribution may be measured using D values corresponding to the 10th, 50th (median), and 90th percentiles of particle size. 10 , D 50 , and D 90 Fillers with a broad particle size distribution can be characterized by one or more of the following: Generally, a high D 90 / D 50 Ratio of, generally high D 90 / D 10 Ratio of, or generally high D 50 / D 10 or any combination thereof. Preferably, D 90 / D 50 is about 3 or more, about 4 or more, about 5 or more, about 6 or more, or about 8 or more. 90 / D 50 The ratio of D may be about 100 or less, or about 40 or less. 90 / D 10 is about 20 or more, about 40 or more, about 60 or more, or about 80 or more. 90 / D 10 The ratio may be about 1000 or less, or about 400 or less. 90 / D 50 The ratio of D may be about 100 or less, or about 40 or less. 50 / D 10 is about 8 or more, about 10 or more, or about 12 or more. 50 / D 10 The ratio of large particles (D 90 The density (characterized by the D value) should be high enough to create sites for the filling of one or more small particles. 90is about 10 μm or more, more preferably about 20 μm or more, even more preferably about 40 μm or more, and most preferably about 60 μm or more. 90 If D is too large, it may be difficult to process the composition. 90 is about 2000 μm or less, more preferably about 1000 μm or less, and most preferably about 500 μm or less. 10 The D values (characterized by the D value) should be small enough so that they can be incorporated into the sites between the large particles. 10 is about 4 μm or less, about 2 μm or less, or about 1 μm or less. Typically, it is difficult and expensive to make very small particles. Therefore, D 10 is preferably about 0.1 μm or greater, or about 0.25 μm or greater, although smaller particles may be used. The conductive filler may have a first portion having an average particle size of about 10 μm or less and a second portion having an average particle size of about 50 μm or greater (preferably, the first portion and the second portion are each present in an amount of about 25 weight percent or greater, about 30 weight percent or greater, or about 35 weight percent or greater of the conductive filler).
[0030] FIG. 1 illustrates the effect of having a broad particle size distribution 6 (B) on the ability to pack small particles 7 between large particles 8 compared to a filler with a narrow particle size distribution 4 (A). With a broad particle size distribution, the particles 2 are closer together as the particle concentration increases and there may be bridges between the two particles due to the matrix phase material 3. The adhesion and / or bridges of the matrix phase to the particle surface may reduce the ability to flow or process the composition. To improve processability, the particles preferably have a surface modifier. For example, (C) has a broad particle size distribution 6 and a coating 5 (e.g., of a surface modifier) to reduce or minimize bonding between the matrix phase material and the filler.
[0031] FIG. 2 is an optical micrograph of an example of a conductive filler, aluminum hydroxide (i.e., Al(OH)3), having a broad particle size distribution.
[0032] Filler surface modifier Although in many filled polymer systems it is desirable to have good compatibility and / or bonding between the matrix phase and the filler phase, the applicant has found that for these highly filled compositions, such compatibility and / or bonding can create bridges between adjacent filler particles that impede the flow of the composition. It is preferred that the matrix phase material does not bond with the surface of the filler. For example, covalent, ionic, and hydrogen bonds may be reduced, minimized, or even completely avoided. This can be achieved by the selection of the matrix phase material and the conductive filler material. Alternatively, the filler material may be treated with one or more surface modifiers to reduce, minimize, or eliminate bonding with the matrix phase material.
[0033] The surface modifier can partially or completely cover the surface of the conductive filler particle. The surface modifier can have one or more functional groups that react with the conductive filler particle. Thus, the surface modifier can be covalently bonded to the conductive filler. As an example, the conductive filler may include an M-OH group (wherein M is a metal atom), and the surface modifier may include a functional group that reacts with the M-OH group to form a direct or indirect bond between the surface modifier and M.
[0034] The surface of the conductive filler may be hydrophobized with a surface modifier. For example, the surface modifier may include an alkyl moiety and one or more functional groups at or near one end of the alkyl moiety. The alkyl moiety preferably includes about 6 or more carbon atoms, more preferably about 8 or more carbon atoms, even more preferably about 10 or more carbon atoms, and most preferably about 12 or more carbon atoms. The one or more functional groups may be selected to react with the surface of the conductive filler. For example, the one or more functional groups may include one or more alkoxysilanes. Such functional groups may be useful for bonding the surface modifier to conductive fillers that include M-OH groups, such as aluminum hydroxide, in particular. An example of a reaction between a conductive filler and a surface modifier is shown in FIG. 3.
[0035] It will be appreciated that the surface modifier may be added to the filler before or after the conductive filler is mixed with the matrix phase material. For example, the conductive filler may be coated and / or reacted with the surface modifier before mixing the conductive filler with the matrix phase material. As another example, the surface modifier may be mixed with the matrix phase material to form a premix, which is then combined with the conductive filler. As another example, the conductive filler may be mixed with the matrix phase material, and then the surface modifier may be added to the mixture.
[0036] As shown in Figure 4(A), when a conductive filler having a narrow particle size distribution is used, even at low filler loadings (e.g., only about 60 weight percent), the resulting composition may have a rough surface. As shown in Figure 4(B), the ability to increase filler loadings is improved by using fillers with a broad particle size distribution. As shown in Figure 4(C), the ability to increase filler loadings is further improved by using fillers with a broad particle size distribution and further by adding a surface modifier that reduces, minimizes, or eliminates bonding between the matrix phase material and the filler particles.
[0037] The combined amount of the matrix phase oligomer or polymer, surface modifier (if present), and one or more fillers (e.g., conductive fillers or ATH) may be about 95 weight percent or more, preferably about 97 weight percent or more, about 99 weight percent or more, or about 100 weight percent, based on the total weight of the composition.
[0038] Purpose Thermal interface materials according to the teachings herein can be used in any device or system requiring a polymeric or oligomeric material with good thermal conductivity. FIG. 5 is a diagram illustrating features of a device 10 including a thermal interface material 12. The device may require a heat flow 20 from a first component 14 of the device to a second component 16 of the device 10. As shown in FIG. 5, the heat flow may pass through the thermal interface material 12. The second component 16 of the device may have a surface 20 (internal or external) that allows for the removal of heat from the second component.
[0039] The thermal interface material can be used as a gap filling material. The thermal interface material can be used as a sealing material. In some applications, it may be necessary to apply a thin layer of the thermal interface material (e.g., about 2 mm or less, about 1 mm or less, about 0.5 mm or less, or about 0.3 mm or less). Thus, the thermal interface material preferably has a low viscosity and / or good mixing behavior (e.g., has a smooth appearance that does not crumble after mixing) so that thin areas or layers can be prepared.
[0040] An article including one or more battery cells, a cell cover having a surface for contacting a cooling unit or a circulating coolant, and a thermal interface material sandwiched between the battery cells and the cell cover. The thermal interface material provides a path for conducting thermal energy from the battery cells to the cell cover to manage the temperature of the battery cells. The battery cells may be provided as one or more modules. Without the thermal interface material, gaps may exist (at least in some areas) between the battery modules and a conductive plate (e.g., of the housing). FIG. 6 is a diagram illustrating features that may be used for thermal management of one or more battery modules. The battery / thermal management system 30 includes a thermal interface material 32 for filling gaps between one or more battery modules 34 and a metal surface 36. The thermal interface material may be applied by placing it on a surface of the battery modules or by placing it on a metal surface. The metal surface may be a cooling plate or other component configured to evacuate heat from the system.
[0041] Test Method Particle size distribution. Unless otherwise specified, the particle size distribution of the filler is measured by laser diffraction.
[0042] Thermal Conductivity Thermal conductivity is measured using a thermal interface material tester manufactured by ZFW Stuttgart. Measurements are performed in Spaltplus mode for thicknesses between 1.8 and 1.2 mm. Absolute thermal conductivity λ (W / mK) is reported. Thermal conductivity can be measured by ASTM 5470.
[0043] Press-in force The press-in force is measured with a tensometer (Zwick). The composition (e.g., gap filling material) is placed on the metal surface. An aluminum piston with a diameter of about 40 mm is placed on top and the material is compressed to an initial position of 5 mm. The material is then compressed from 5 mm to 0.3 mm at a speed of about 1 mm / s, and the force-deflection curve is recorded. The force (N) at a thickness of 0.5 mm is then recorded in a data table and considered as the press-in force. A material with low viscosity has a press-in force of 700 N or less. A material with high viscosity has a press-in force of more than 700 N or about 800 N or more. A material with low viscosity has a press-in force of preferably about 600 N or less, even more preferably about 500 N or less, and most preferably about 400 N or less.
[0044] mixing ability The ability to mix the compositions was judged by the ability to produce a single mass of material with a smooth surface. Such a material has a "good" mix. If the surface is rough and / or the material falls apart when removed from the mixer, the mix is poor.
[0045] material POLYOL-1 is a glycerin initiated propylene oxide polyether triol with an equivalent molecular weight of about 1800 g / mol and an OH number of about 35 mg KOH / g. Its average molecular weight is about 4800 g / mole. POLYOL-1 is a liquid at room temperature and does not have any glass transition temperature above 5° C. The oligomer is partially capped (about 11%) with ethylene oxide.
[0046] ATH-1 is an aluminum hydroxide with a broad particle size distribution. ATH- is believed to have a bimodal particle size distribution. The amount of Al(OH)3 is about 99.7 weight percent. The particle size distribution is characterized in Table 1. The filler is characterized by a sieve retention of about 35% when using a 45 μm sieve. The broad and / or bimodal particle size distribution of ATH-1 is shown in FIG. 2. The average size of the smaller particles is less than about 10 μm and the average size of the larger particles is greater than about 50 μm.
[0047] ATH-2 is an aluminum hydroxide having a generally narrow particle size distribution. ATH-2 is generally considered to have a monomodal particle size distribution. The amount of AL(OH)3 is about 99.4 weight percent. The particle size distribution profile is shown in Table 1. ATH-2 is characterized by a sieve residue of about 0.2% when using a 45 μm sieve.
[0048] DYNASYLAN® 9116 is a silane-containing compound available from EVONIK, which comprises or consists essentially of hexadecyltrimethoxysilane.
[0049] [Table 1] EXAMPLES
[0050] The loaded compounds are prepared in a planetary mixer or on a dual asymmetric centrifuge. First, the liquid materials (i.e., the surface modifier and the matrix phase material) are mixed together under vacuum. The filler is then added and the composition is mixed for 30 minutes.
[0051] Examples 1-8 were prepared using ATH-2, a filler that generally has a narrow particle size distribution. In Examples 1-4, the liquid material was VORANOL™ CP4610 and the compositions consisted only of the filler and VORANOL™ CP4610. The concentrations of the filler and matrix phase in the compositions are shown in Table 2. In Examples 5-8, the compositions contained ATH-2, VORANOL™ CP4610, and DYNASYLAN® 9116 in the amounts shown in Table 3.
[0052] [Table 2]
[0053] [Table 3]
[0054] Examples 9-16 were prepared using ATH-1, a filler that typically has a broad particle size distribution. In Examples 9-12, the liquid material was VORANOL™ CP4610 and the compositions consisted only of the filler and VORANOL™ CP4610. The concentrations of the materials in these compositions are shown in Table 4. In Examples 13-18, the compositions contained ATH-1, VORANOL™ CP4610, and DYNASYLAN® 9116 in the amounts shown in Table 5.
[0055] [Table 4]
[0056] [Table 5]
[0057] As can be seen in Table 4, the use of a broad particle size distribution of filler improved the incorporation of the filler into the composition. Good mixing (compositions with smooth surfaces) was obtained for compositions containing 78.1% and 84.7% filler. However, at higher filler levels, the surface became rough and mixing was poor. Additionally, the viscosity, measured by 0.5 mm indentation force, was high.
[0058] As seen in Table 5, broad size distribution filler in combination with a silane surface modifier allowed for higher filler incorporation and lower viscosity. Even at 90.85 weight percent filler loading (Example 16), the mixture was good, the surface was smooth, and the viscosity was low as measured by 0.5 mm indentation force.
[0059] Press-in Force: The press-in force is measured using a dynamometer (Zwick). The gap filler material is placed on the metal surface. An aluminum piston with a diameter of 40 mm is placed on top of it and compresses the material to 5 mm (initial position). The material is then compressed to 0.3 mm at a rate of 1 mm / s and the force-displacement curve is recorded. The force (N) at a thickness of 0.5 mm is then entered into a data table and considered as the press-in force. The invention as originally claimed in the present application is set forth below. [1] A composition comprising: i. a continuous matrix phase comprising an oligomer or polymer; ii. a dispersed filler phase comprising one or more fillers dispersed within the matrix phase; Including, The one or more fillers have a D of about 3 or more. 90 / D 50 having a broad particle size distribution characterized by the ratio of; A composition comprising one or more fillers that are coated with and / or reacted with a surface modifier. [2] The composition according to [1], wherein the composition is a thermal interface material having a thermal conductivity of about 2.0 W / mK or more (preferably about 2.5 W / mK or more, more preferably about 3.0 W / mK or more). [3] The composition according to [1] or [2], wherein the one or more fillers are conductive fillers (i.e., thermally conductive fillers) having a thermal conductivity of about 3 W / mK to about 80 W / mK. [4] The composition according to any one of [1] to [3], wherein the conductive filler has a thermal conductivity of about 60 W / mK or less (e.g., about 40 W / mK or less, or about 20 W / mK or less). [5] The composition according to any one of [1] to [4], wherein the conductive filler contains one or more metal atoms, and the concentration of the one or more metal atoms is about 25 percent or less, based on the total number of atoms in the conductive filler. [6] The composition according to any one of [1] to [5], wherein the conductive filler contains aluminum hydroxide. [7] The composition according to any one of [1] to [6], wherein the conductive filler has a Mohs hardness of about 6 or less, preferably about 5 or less, and more preferably about 4 or less. [8] The composition according to any one of [1] to [7], wherein the oligomer or polymer has a weight average molecular weight of about 15,000 g / mol or less, or about 10,000 g / mol or less. [9] The composition according to any one of [1] to [8], wherein the oligomer or polymer contains an alkoxide group.
[10] The composition according to any one of [1] to [9], wherein the surface modifier comprises an alkyl group having about 6 or more (preferably about 8 or more, or about 10 or more, or about 12 or more) carbon atoms and a functional group covalently bonded to the filler at one end.
[11] The composition according to any one of [1] to
[10] , wherein the surface modifier is present in an amount of about 0.05 weight percent or more (preferably about 0.2 weight percent or more, more preferably about 0.5 weight percent or more), based on the total weight of the composition.
[12] The composition according to any of [1] to
[11] , wherein the surface modifier is present in an amount of about 10 weight percent or less, preferably about 8 weight percent or less, more preferably about 6 weight percent or less, and most preferably about 4 weight percent or less.
[13] The composition described in any of [1] to
[12] , wherein the amount of the one or more fillers is about 86 weight percent or more, based on the total weight of the composition.
[14] The composition described in any of [1] to
[13] , wherein the amount of the one or more fillers is about 95 weight percent or less.
[15] The composition according to any one of [1] to
[14] , wherein the one or more functional groups of the surface modifier include an alkoxysilane group.
[16] A composition comprising: i. a continuous matrix phase comprising a polymer or polymerizable compound; ii. about 86 weight percent or greater of a dispersed filler phase comprising one or more conductive fillers dispersed within the matrix phase; Including, The one or more conductive fillers have a D of about 3 or more. 90 / D 50 The composition has a broad particle size distribution characterized by the ratio of
[17] The composition, i) the composition mixes as a smooth mass without crumbling; and / or ii) the composition has a viscosity of about 700 N or less (measured by an indentation force of 0.5 mm); and / or iii) the composition has a thermal conductivity of about 3 W / mK or greater; The composition according to any one of [1] to
[16] , characterized in that:
[18] An article comprising: The first ingredient that produces heat; a second component for removing heat; and a layer of the composition according to any one of [1] to
[17] , inserted between the first component and the second component; Including, The article, wherein the layer provides a path for heat flow from the first component to the second component.
[19] The article of
[18] , wherein the first component comprises a battery.
[20] A method for cooling a device, comprising: generating heat in the first component; transferring the heat to a second component by flowing the heat through a thermal interface component; Including, The method according to any one of claims [1] to
[17] , wherein the thermal interface component is formed from the composition described in any one of claims [1] to
[17] .
Claims
1. 1. A composition comprising: i. a continuous matrix phase comprising an oligomer or polymer; ii. a dispersed filler phase comprising one or more conductive fillers dispersed within the matrix phase; Including, the oligomer or polymer comprises an alkoxide group; the conductive filler comprises aluminum hydroxide; The conductive filler has a D of 3 or more. 90 / D 50 having a broad particle size distribution characterized by the ratio of A composition comprising a conductive filler that is coated with and / or reacted with a surface modifier.
2. 10. The composition of claim 1, wherein the composition is a thermal interface material having a thermal conductivity of 2.0 W / mK or greater.
3. The composition according to claim 1 or 2, wherein the conductive filler is a conductive filler having a thermal conductivity of 3 W / mK to 80 W / mK.
4. The composition according to any one of claims 1 to 3, wherein the conductive filler has a thermal conductivity of 60 W / mK or less.
5. The composition of any one of claims 1 to 4, wherein the conductive filler has a Mohs hardness of 6 or less.
6. The composition according to any one of claims 1 to 5, wherein the oligomer or polymer has a weight average molecular weight of 15,000 g / mol or less.
7. The composition of any one of claims 1 to 6, wherein the surface modifier comprises an alkyl group having six or more carbon atoms and a functional group covalently bonded at one end to the filler.
8. The composition of any one of claims 1 to 7, wherein the surface modifier is present in an amount of 0.05 weight percent or greater, based on the total weight of the composition.
9. The composition of any one of claims 1 to 8, wherein the surface modifier is present in an amount of 10 weight percent or less.
10. The composition of any one of claims 1 to 9, wherein the amount of the one or more fillers is 86 weight percent or greater, based on the total weight of the composition.
11. The composition of any one of claims 1 to 10, wherein the amount of the one or more fillers is up to 95 weight percent.
12. The composition of any one of claims 1 to 11, wherein the one or more functional groups of the surface modifier comprise an alkoxysilane group.
13. 1. A composition comprising: i. a continuous matrix phase comprising a polymer or a polymerizable compound; ii. a dispersed filler phase comprising 86 weight percent or more of one or more conductive fillers dispersed within the matrix phase; Including, the conductive filler comprises aluminum hydroxide; The conductive filler has a D of 3 or more. 90 / D 50 having a broad particle size distribution characterized by the ratio of The conductive filler is coated with and / or reacted with a surface modifier; composition.
14. The composition comprises: i) the composition mixes as a smooth material without crumbling; and / or ii) the composition has a viscosity of 700 N or less (measured by an indentation force of 0.5 mm); and / or iii) the composition has a thermal conductivity of 3 W / mK or greater; Composition according to any one of claims 1 to 13, characterized in that it comprises one or various combinations of:
15. An article, a first component that produces heat; a second component for removing heat; and a layer of the composition of any one of claims 1 to 14 interposed between the first component and the second component; Including, The article, wherein the layer provides a path for heat flow from the first component to the second component.
16. The article of claim 15 , wherein the first component comprises a battery.
17. 1. A method for cooling a device, comprising: generating heat in the first component; transferring the heat to a second component by flowing the heat through a thermal interface component; Including, The method of claim 1, wherein the thermal interface component is formed from the composition of any one of claims 1 to 14.
Citation Information
Patent Citations
Heat-conductive polymer composition and heat-conductive molding
JP2002097372A
Polyphenylene sulfide resin composition
JP2007302822A
Heat conductive silicone composition and cured product of the same
JP2011178821A
Heat dissipation member for solar cell module, and solar cell module employing the same
JP2017139842A
High performance thermal interface materials with low thermal impedance
JP2018502946A